Impaired autophagy flux contributes to enhanced ischemia reperfusion injury in the diabetic heart - Jialing Tang; Nanyoung Yoon; Keith Dadson; Hye Kyoung Sung; Yubin Lei; Thanh Q. Dang; Wing Yan Chung; Saher Ahmed; Ali A. Abdul-Sater; Jun Wu; Ren-Ke Li; James Jonkman; et al. (Autophagy Reports)
Myocardial ischemia/reperfusion (I/R) injury is exacerbated in diabetic individuals and animal models. We tested whether autophagy is an important cellular determinant of cell death. First, we utilized a cellular model of hypoxia reoxygenation (H/R) in H9c2 cells cultured in low or high glucose (HG) and tested cell death using flow cytometry to detect Annexin-V and propidium iodide, imaging cell viability ReadyProbe and lactate dehydrogenase release. We observed that cell death induced by H/R was enhanced by HG. Kinetic analysis of caspase-3 activity using a fluorescence reporter probe, stable expression of the VC3AI biosensor and western blotting indicated that H/R induced activation of caspase-3 was enhanced by HG. Temporal autophagy flux analysis using DapRed and DalGreen probes indicated an initial increase in response to H/R that was reduced upon prolonged (24h) R. HG suppressed this induction of autophagy. This was verified using LC3 HiBiT reporter assay, tandem-fluorescent LC3, and western blotting. Lysosomal cathepsin activity was also elevated at 6h and suppressed at 24h R. Autophagy-deficient cells were generated via CRISPR-mediated knockout of atg7 and the effect of combined HG and H/R treatment on caspase activation and cell death was elevated in comparison with wild type cells. We then performed coronary artery ligation surgery to induce ischemia, followed by reperfusion, in wild-type or streptozotocin (STZ)-induced hyperglycemic mice. Non-invasive 3-dimensional imaging using fluorescence molecular tomography combined with computerized tomography was employed to monitor spatio-temporal activation of cardiac autophagy and apoptosis. Upon systemic injection of a near infra-red cathepsin activatable probe we found that hyperglycemic mice had lower activity in the infarct region after I/R versus wild type. In parallel, we observed a higher extent of I/R-induced apoptosis, detected with an annexin-V probe, in hyperglycemic mice. Collectively, these results revealed that impaired autophagic flux in the presence of high glucose levels exacerbates I/R injury.Abbreviation: satg7, autophagy-related 7; FMT, fluorescence molecular tomography; HG, high glucose; H/R, hypoxia/reoxygenation; I/R, ischemia/reperfusion; LC3, MAP1LC3; N, normoxia; NG, normal glucose; NIR, near-infrared; p62, SQSTM1; STZ, streptozotocin.